2016
DOI: 10.1073/pnas.1525059113
|View full text |Cite
|
Sign up to set email alerts
|

Waltzing route toward double-helix formation in cholesteric shells

Abstract: Liquid crystals, when confined to a spherical shell, offer fascinating possibilities for producing artificial mesoscopic atoms, which could then self-assemble into materials structured at a nanoscale, such as photonic crystals or metamaterials. The spherical curvature of the shell imposes topological constraints in the molecular ordering of the liquid crystal, resulting in the formation of defects. Controlling the number of defects, that is, the shell valency, and their positions, is a key success factor for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
47
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…Besides, unexpected symmetries/valencies have been recently reported in cholesteric shells [16,17], in which there is a spontaneous helical arrangement of the director field. Remarkably, it is possible to achieve a good control over the equilibrium defect positions by tuning the shell thickness heterogeneity [13,16,18]. This feature could then be further exploited to produce shells with a variable bonding directionality.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Besides, unexpected symmetries/valencies have been recently reported in cholesteric shells [16,17], in which there is a spontaneous helical arrangement of the director field. Remarkably, it is possible to achieve a good control over the equilibrium defect positions by tuning the shell thickness heterogeneity [13,16,18]. This feature could then be further exploited to produce shells with a variable bonding directionality.…”
mentioning
confidence: 96%
“…Since Nelson's seminal paper, many experimental studies focused on nematic shells have demonstrated the applicability of such concepts [12][13][14][15]. Besides, unexpected symmetries/valencies have been recently reported in cholesteric shells [16,17], in which there is a spontaneous helical arrangement of the director field. Remarkably, it is possible to achieve a good control over the equilibrium defect positions by tuning the shell thickness heterogeneity [13,16,18].…”
mentioning
confidence: 99%
See 3 more Smart Citations